Wetland birds : habitat resources and conservation implications - Weller, Milton Webster (Cambridge University Press, 1999)
Birds are important indicators of water quality in wetlands of all descriptions. In this readable account, Milton Weller describes the ecology of wetland birds in terms of resource use providing a wealth of practical and basic information for professionals and keen birders alike.